1984
DOI: 10.1159/000194618
|View full text |Cite
|
Sign up to set email alerts
|

Ventilatory and Occlusion Pressure Responses to Hypercapnia in Patients with Chronic Renal Failure

Abstract: Little is known of the effect of chronic renal failure (CRF) on ventilatory regulation. In 38 subjects (19 healthy, 19 with CRF before and after dialysis), we performed measurements of ventilation (VE) and occlusion pressure (P0.1) while the subjects were breathing air and hypercapnic gas mixtures. The results have shown that (1) during air ventilation, CRF patients exhibited lower values of VE and P0.1, which returned to normal after dialysis; (2) during hypercapnic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

1987
1987
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 6 publications
0
8
0
2
Order By: Relevance
“…To the best of our knowledge there are a few studies examining P 0.1 before and immediately after hemodialysis maintenance therapy [25, 26] in ESKD patients. In spontaneous breathing patients Sebert et al [26] examined the patient's P 0.1 relationship with the V E at different CO 2 concentrations, before and after hemodialysis maintenance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To the best of our knowledge there are a few studies examining P 0.1 before and immediately after hemodialysis maintenance therapy [25, 26] in ESKD patients. In spontaneous breathing patients Sebert et al [26] examined the patient's P 0.1 relationship with the V E at different CO 2 concentrations, before and after hemodialysis maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…In spontaneous breathing patients Sebert et al [26] examined the patient's P 0.1 relationship with the V E at different CO 2 concentrations, before and after hemodialysis maintenance. They found that for the same V E response CKD patients needed a higher neuromuscular ventilatory drive than normal subjects.…”
Section: Discussionmentioning
confidence: 99%
“…A larger number of patients and a control group were included in this study. Although on air CRF patients had lower VE and P0,1 compared to controls, the hypercapnic response of P0,1 and the apneic threshold were increased [127].…”
Section: Pathogenesis Of Sdb In Crfmentioning
confidence: 69%
“…The increased response had returned to baseline at 24 hours [125]. Sebert P et al report that HD did not change the slope of the response of P0,1 to hypercapnic stimulation but shifted the curve upwards [127], resulting to a lower apneic threshold and an increased minute ventilation for the same PCO 2 . Other investigators did not report increased sensitivity to CO 2 immediately after HD [126,132].…”
Section: Pathogenesis Of Sdb In Crfmentioning
confidence: 95%
See 1 more Smart Citation